The Implementation of The Role-Playing Learning Method in Improving Students’ Mastery of Arabic Vocabulary At Smpit Nur Hidayah Surakarta - Hanana NidaanKhofiiya; Zahrodin Fanani (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
Some students experienced difficulties in understanding the material delivered. This was due to the teaching method used by the Arabic language teacher at SMPIT Nur Hidayah Surakarta, which relied on lectures and memorization. This learning strategy was applied continuously in every Arabic language lesson, resulting in boredom and low student motivation. This type of research is classroom action research (CAR) using the Kurt Lewin model. The research subjects were 35 eighth-grade students (class VIII A) of SMPIT Nur Hidayah Surakarta. The study consisted of two cycles, and each cycle included four stages: planning, implementation, observation, and reflection. Data collection techniques involved observation, documentation, tests, and interviews. The findings of this study show that the use of the role-playing method can improve the mastery of Arabic vocabulary (mufrodat) among class VIII A students at SMPIT Nur Hidayah. This is evidenced by an increase in vocabulary mastery, with the class average score rising from 74.8 in cycle I to 83.4 in cycle II. This indicates that students experienced an improvement of 8.6%. The improvement occurred after the researcher implemented several stages of action, namely: (1) the teacher explained the implementation technique and assigned students to play roles, (2) the teacher divided students into small groups consisting of four members, (3) each student acted out their assigned role referring to the material a‘dhā’ul jism, and (4) each group performed alternately. The advantages of this method include students showing greater enthusiasm for learning because they were directly involved in role-playing activities. They not only memorized vocabulary but also practiced it in real conversational contexts. However, the weaknesses include students’ limited vocabulary mastery; many still mispronounced words or could only use simple vocabulary. Teachers also faced challenges in maintaining a conducive classroom environment, as some students considered the activity merely a game